COMPARATIVE STUDY OF E-WALLET USAGE AMONG SMALL VENDORS IN URBAN AND RURAL AREAS OF BHANDARA DISTRICT - Dongardiveprav, Roshan Raibhanji; Deshmukh, Meena Anil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancement of digital payment technology in India has brought about significant changes in the transaction patterns of various economic sectors. However, the adoption and usage of e-wallets among small vendors, who are an important component of the informal sector, is not the same in urban and rural areas. The present study presents a comparative analysis of e-wallet usage among small vendors in urban and rural areas of Bhandara district. For this study, primary data was collected from 320 vendors (160 urban and 160 rural) through a structured questionnaire. Based on this information, the level of awareness, frequency of use, perceived benefits and barriers to adoption of e-wallets were studied. The findings revealed significant differences between urban and rural areas. Urban vendors showed higher levels of digital literacy, easier access to smartphones and higher use of e-wallets for business transactions. In contrast, rural vendors face challenges such as limited internet connectivity, lack of trust in digital platforms and low awareness. The study highlights the need for focused interventions such as digital literacy training, infrastructure development and policy support to increase financial inclusion and achieve similar digital transformation in urban and rural areas.